Connecting Diverse Communities Through Citizen Science Data Infrastructure - Hammock, Jen; Wiggins, Andrea (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
The BioCubes project is a citizen science biodiversity observation and reporting protocol designed for group participation in classroom and non-formal education settings. A two-year study will develop a proof-of-concept information technology infrastructure to support distribution and use of data from BioCubes across the US. The goal of this work is promoting novel STEM learning opportunities for diverse student populations while demonstrating the feasibility of exchanging and integrating citizen science data with ongoing biodiversity research, a key step in advancing citizen science. In this abstract, we briefly introduce key features of our project and identify several considerations for the design of the sociotechnical systems to support both data contributors and data users.